Pengaruh Parameter Proses Electrospinning pada Komposit Polyvinylidene Fluoride/Polyacrylonitrile Nanofiber - Ida Sriyanti; Muhammad Rama Almafie; Rahma Dani; Meutia Kamilatun Nuha Ap Idjan; Radiyati Umi Partan; M Rudi Sanjaya; Jaidan Jauhari (Jurnal Penelitian Pendidikan IPA, 2023)
PAN cannot be used as a stand-alone nanofiber, so it needs to be modified through copolymerization with other polymers, such as PVDF. It is composite mutually beneficial for both PVDF/PAN polymers. Study aims to see the effect of process parameters, such as voltage, flow rate and needle tip distance of PVDF/PAN composite nanofiber as well as molecular interaction and crystal structure, to confirm the presence of polymer in the nanofiber composite. The nanofibers with solution parameters PN1: PVDF 6% and PAN 8%, PN2: PVDF 6% and PAN 10%, and PN3: PVDF 6% and PAN 12% were prepared using electrospinning. Morphology of the process parameters of voltage (12kV, 16kV, 18kV), flow rate (30 Î¼l/min, 60 Î¼l/min, 90 Î¼l/min) and needle tip distance (75 mm, 100 mm, 125 mm) were observed. The results showed straight and continuous fibre morphology, with a smooth surface and no beaded structure, with homogeneous fibre distribution with an increase in diameter from 394 Â± 79 nm (NF1) to 851 Â± 89 nm (NF3). The optimal state was in the solution of PN2: PAN 10% (w/w) and PVDF 6% (w/w), High Voltage 12 kV, Flow Rate PN3: 60 Î¼l/min, and Needle to Collector Distance 75 mm.